Evaluation of bioactivities of morinda tinctoria leaves extract for pharmacological applications - Thangavel Sivakumar (2018)
© 2018 The Authors. Objective: The present study was aimed to prepare Morinda tinctoria leaves extracts with the different solvent system and to evaluate the bioactivities. Methods: The extracts of M. tinctoria were qualitatively analyzed for the primary phytochemical content. The functional groups of extract were determined by Fourier-transform infrared spectroscopy (FT-IR) analysis. The antimicrobial properties were determined by plate assays. The antioxidant and in vitro anti-inflammatory properties and membrane stabilizing nature of aqueous extract of M. tinctoria (AEM) were measured using a spectrophotometer. Results: The aqueous, ethanolic, and acetone extracts of M. tinctoria were prepared. AEM contains quinones, steroids, terpenoids, phenols, glycosides, and tannins. FTIR result showed that AEM comprises of alkyl halides, 1°, 2° amines, aromatics, aliphatic amines, alcohols, carboxylic acids, esters, ethers, and alkanes, saturated aliphatic, and phenolic groups. The antimicrobial property of M. tinctoria varied based on the solvent used for the extraction. About 86.90±0.36, 78.58±0.13, and 80.33±0.09% of total antioxidant capacity, reducing power, and hydrogen peroxide scavenging activity were observed in AEM, respectively. The 1, 1- diphenyl 2-picrylhyorazyl and 2, 2-Azinobis-(3 ethylbenzothiazoline-6-sulfonic acids) assay results indicated 85.20±0.50 and 52.41±0.60% of free radical scavenging activity in AEM. The protease activity (44.10±0.26%) and protein degradation (44.38±0.58%) were proscribed by AEM. AEM prevents 69.36±0.20% of cell lysis. Conclusion: The results revealed that the AEM leaves were harmless and enriched with potent bioactive principles, which is further used for food and pharmacological applications.